Self-compassion and emotional invalidation mediate the effects of parental indifference on psychopathology. (30th August 2016) - Westphal, Maren; Leahy, Robert L.; Pala, Andrea Norcini; Wupperman, Peggilee
Abstract: This study investigated whether self-compassion and emotional invalidation (perceiving others as indifferent to one's emotions) may explain the relationship of childhood exposure to adverse parenting and adult psychopathology in psychiatric outpatients ( N =326). Path analysis was used to investigate associations between exposure to adverse parenting (abuse and indifference), self-compassion, emotional invalidation, and mental health when controlling for gender and age. Self-compassion was strongly inversely associated with emotional invalidation, suggesting that a schema that others will be unsympathetic or indifferent toward one's emotions may affect self-compassion and vice versa. Both self-compassion and emotional invalidation mediated the relationship between parental indifference and mental health outcomes. These preliminary findings suggest the potential utility of self-compassion and emotional schemas as transdiagnostic treatment targets. Highlights: We examined associations between self-compassion, invalidation, and psychopathology. Path analysis was used with data from a sample of 326 psychiatric outpatients. Self-compassion was strongly inversely associated with emotional invalidation schema. Self-compassion and invalidation mediated adverse parenting-psychopathology relation. Self-compassion and emotional schemas may present transdiagnostic treatment targets.